Pharmacokinetics of the systemic application of hyaluronic acid for joint arthritis treatment - Šimek, Matěj; Rubanová, Daniela; Nešporová, Kristina; Skoroplyas, Svitlana; Lehká, Kateřina; Raptová, Petra; Velebný, Vladimír; Kubala, Lukáš (International journal of biological macromolecules, 2025)
Frequent degenerative joint diseases, known as arthritis, are characterized by joint inflammation and cartilage breakdown. Various arthritis types are traditionally managed with intraarticular injections of hyaluronan or its derivatives. However, intravenous administration of hyaluronan is emerging as a vital alternative, particularly because intraarticular injections can be challenging for clinicians when targeting small or swollen joints. Pharmacokinetics of intravenously and intraperitoneally administered middle-Mw hyaluronan were studied in an adjuvant-induced arthritis mouse model alongside therapeutic effects. Using 13C-, biotin- and fluoresce-labeling, we found hyaluronan accumulated in inflamed joint tissues while distribution in other organs remained similar to healthy controls. Repeated administrations significantly reduced arthritis symptoms like swelling and redness, RANKL, inducible nitric oxide synthase, COMP and prostaglandin E2 levels. Moreover, hyaluronan treatment prevented dextran-FITC penetration into inflamed paws suggesting reduced vascular permeability at the site of inflammation. These findings support systemic hyaluronan administration as a promising arthritis treatment strategy.
Keywords: Animals; Stable isotope; Female; Rheumatoid arthritis; Intraperitoneal; Hyaluronan; ženské pohlaví; Intravenous; Vascular leakage; injekce intraartikulární; Mice; Pharmacokinetics; klouby; Injections, Intra-Articular; injekce intravenózní; kyselina hyaluronová; myši; Hyaluronic Acid; Inflammation; Joints; Arthritis, Experimental; modely nemocí na zvířatech; Disease Models, Animal; zvířata; artritida experimentální; Injections, Intravenous